Treatment for Spondylolysis and Spondylolisthesis in Children - Andreas Leonidou (Journal of Orthopaedic Surgery, 2015)
Purpose. To review outcome of 44 children who underwent conservative or surgical treatment for spondylolysis or spondylolisthesis. Methods. Records of 25 male and 19 female children aged 5 to 14 (mean, 10.2) years who underwent conservative (n=39) or surgical (n=5) treatment for spondylolysis (n=19) or spondylolisthesis (n=25) were reviewed. Conservative treatment involved application of a thoracolumbosacral orthotic brace for all day except bedtime until symptoms resolved and then physiotherapy including exercises to strengthen the abdominal and back muscles and stretching exercises of the hamstrings and hip flexors. Surgery (instrumented posterolateral fusion [n=4] or Wiltse posterolateral fusion [n=1]) with allografts was indicated in patients with refractory pain (n=2) or nerve root irritation (n=1) and in patients with iatrogenic spondylolisthesis (n=2), followed by application of the brace for 3 months and then physiotherapy. Outcome was assessed using the Seitsalo scoring system. Results. The mean follow-up period was 6.5 (range, 3–10) years. No patient developed any postoperative complication. Outcome was excellent in 35 patients, good in 8, and fair in one. All 5 patients who underwent posterolateral fusion for refractory spondylolisthesis achieved good outcome. In 11 patients with spondylolysis, the pars defect healed. None of the spondylolysis progressed to spondylolisthesis. All displacements remained stable, without any progression. Conclusion. Conservative treatment is effective for most patients with spondylolysis or spondylolisthesis. Instrumented posterolateral fusion is indicated in patients with persistent symptoms and for iatrogenic cases.